Uh-oh: Frances Stark 1991-2015 - Subotnick, Ali 1972- (Delmonico Books, Prestel, 2015)
"This generously illustrated book offers the first comprehensive overview of the work of the Los Angeles-based interdisciplinary artist Frances Stark."